ON THE INFLUENCE OF THE SHAPE OF ANODE VOLTAGE PULSE ON THE OPERATION STABILITY OF SPATIAL-HARMONIC MAGNETRON WITH COLD SECONDARY EMISSION CATHODE - V. А. Markov; V. D. Naumenko (Радиофизика и электроника, 2018)
One of the main problems faced by developers of modulators for spatial-harmonic magnetrons with cold secondary emission cathode is the selection of the correct shape of an anode voltage pulse that will ensure the stable operation of the magnetron. In this paper, the effect of the shape of the anode voltage pulse on the operation of transmitters based on magnetrons with cold secondary emission cathodes is investigated. The influence of different parts of the pulse on such parameters of the magnetron as the required current of the starting cathode necessary for stable excitation of secondary emission from the cold cathode, the stability of operation on the selected mode of oscillation, and the generation of the maximum power is experimentally studied. It is shown that the magnitude of the starting cathode current is determined, first of all, by the steepness of the pulse front. Its optimum value is usually about 150 kV/ms. In this case, starting cathode should provide a current of only a few tens of milliamperes, which can significantly increase the lifetime of the device. The article also shows that the presence of a pulse spike at the beginning of a voltage pulse facilitates a premature transition to a non-working mode of oscillation. As a result, this leads to a decrease in the output power of the magnetron. The duration of the decay determines the ability of the magnetron to operate at small pulse duration. For very short pulses, the energy expended on the microwave generation can be equal to the energy expended on the formation of the pulse decay. As a result, it was concluded that the usage of spatial-harmonic magnetrons with cold cathode requires a careful refinement of the characteristics of a pulse modulator. The steepness of the front of its output pulse should be about 150 kV/ms, and the pulse spike at the beginning of the voltage pulse should be as small as possible. When working on very short pulses it is necessary to provide a longer rate of pulse decay.